Processual-Phenomenological Optimization of Treatment for Random Pattern Trending Curanmor by Resmob Subnit at Nganjuk Police - Christoper, Kevin William (Police Studies Review, 2024)
Random pattern trend is the type of daily motor vehicle theft case known that happens in the Nganjuk Police Legal Area from poverty issue. This case frequently results in these acts falling outside the purview of the Nganjuk Police Reserse Mobile’s analysis and evaluation (anev). It uses participation observation that asking questions about how to maximize the criminal clearance rate without answerrestricting and participating in real time situations from October to December 2023. The 3 subjects who were addressed in which ran are members of the Nganjuk Police Reserse Mobile, perpetrators, and victims (society). The last research utilizes perspective of processual-phenomenology with theorems of 6M, SWOT, social change, police change, and reserse mobile. Processual finds out how the normative work of standar operational procedure synchornize in literature review. Phenomenology declares the actual problem in which lies on the field work. By processual side, the Nganjuk Police Reserse Mobile has been consistent with the usage by personnel management, aggressor has been consistent by socioeconomic poverty, and victims have been consistent of the reporting by total networking acts. The Nganjuk Police Reserse Mobile, on the other hand, has been discovered to have a phenomenological side with little usage of technology (CCTV), underpowered number of personnel, and how the usage of social media being optimized. As thus, it recommends for optimalizations such employing well-distributed personnel and developing more suitable monitoring technology. Penultimately, police culture ought to be embraced with distributing community policing partnerships with the National Police.